2013
DOI: 10.1186/1465-9921-14-26
|View full text |Cite
|
Sign up to set email alerts
|

Exploring factors influencing asthma control and asthma-specific health-related quality of life among children

Abstract: BackgroundLittle is known about factors contributing to children’s asthma control status and health-related quality of life (HRQoL). The study objectives were to assess the relationship between asthma control and asthma-specific HRQoL in asthmatic children, and to examine the extent to which parental health literacy, perceived self-efficacy with patient-physician interaction, and satisfaction with shared decision-making (SDM) contribute to children’s asthma control and asthma-specific HRQoL.MethodsThis cross-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(72 citation statements)
references
References 40 publications
7
63
0
2
Order By: Relevance
“…Reinforcing it in parents, guardians, and patients has the potential to improve the capacity of self-management of chronic illnesses, especially childhood asthma (17) . A study carried out in Florida, United States (30) , concluded that parents with a high perceived selfefficacy also showed better results in control parameters of the disease, corroborating the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…Reinforcing it in parents, guardians, and patients has the potential to improve the capacity of self-management of chronic illnesses, especially childhood asthma (17) . A study carried out in Florida, United States (30) , concluded that parents with a high perceived selfefficacy also showed better results in control parameters of the disease, corroborating the findings of the present study.…”
Section: Discussionsupporting
confidence: 90%
“…They found no relationship between parent health literacy and child asthma control or healthcare utilization. 32 Ghandi et al 33 report an indirect relationship only between parent health literacy measured by the s-TOFHLA 34 and child asthma control measured by 10 items. 44 The discrepancy in our findings with these previously reported results may reflect differences in the samples or the measures used to assess health literacy and/or asthma control.…”
Section: Discussionmentioning
confidence: 99%
“…Lower parent health literacy has been associated with more healthcare utilization by children with asthma in some studies, 29,30 but not in others. 31,32 Two studies examining parent health literacy and child asthma control have disparate findings: one reports an indirect relationship between health literacy and asthma control through satisfaction with shared decision making, 33 while the other found no relationship. 32 This study examines the role of parent health literacy in pediatric asthma health outcomes, including asthma control, healthcare utilization, and school days missed due to asthma.…”
Section: Introductionmentioning
confidence: 99%
“…Frequent urgent health care utilization and younger age have been shown to be associated with more disease burden for children with asthma, their families and the health care system [3][4][5][6][7]. High rates of urgent care use for asthma are associated with residing in low income and minority communities [8][9][10].…”
Section: Introductionmentioning
confidence: 99%